The EU proposal for a Carbon Border Adjustment Mechanism: an advanced tool to combat ‘carbon leakage’ , a new EU own resource of ‘moral suasion’ for third Countries? - Selicato, Gianluca (Review of European and Comparative Law, 2022)
With the proposal for a Regulation of the European Parliament and of the Council establishing a Carbon Border Adjustment Mechanism (CBAM) adopted on July 14, 2021 by the European Commission, it begins to reach the heart of the global debate on the opportunity to adopt mechanisms to combat the phenomenon of ‘carbon leakage’, that is the attempt to evade existing carbon pricing systems through the delocalization of the most polluting activities. In this way, the European Union demonstrates its serious intention to strengthen actions against climate change and to identify customs taxation as an instrument to guide the choices of its trading partners and, therefore, of the major world economies. The precautions adopted in the application of the CBAM and the long transitional period before its entry into force, however, prevent the full appreciation of its potential repercussions (also) in terms of the new own resource of the European budget.